2017
DOI: 10.1111/asj.12920
|View full text |Cite
|
Sign up to set email alerts
|

Heifers express G‐protein coupled receptor 153 in anterior pituitary gonadotrophs in stage‐dependent manner

Abstract: We recently found that orphan G-protein-coupled receptor (GPR)153 is expressed in the anterior pituitary (AP) of heifers, leading us to speculate that GPR153 colocalizes with gonadotropin-releasing hormone receptor (GnRHR) in the plasma membrane of gonadotrophs and is expressed at specific times of the reproductive cycle. To test this hypothesis, we examined the coexpression of GnRHR, GPR153, and either luteinizing hormone or follicle-stimulating hormone in AP tissue and cultured AP cells by immunofluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…6c) colocalize with GnRHRs in the limited area of the plasma membrane in bovine gonadotrophs. The positive overlap coefficient calculated by confocal data analysis software was very strong (more than 0.70) between GnRHR and GPR61, between GnRHR and GPR153, and between GnRHR and AMHR2 on the cell-surface of gonadotrophs [33][34][35].…”
Section: Colocalization Of Gpr61 Gpr153 and Amhr2 With Gnrhr In Thementioning
confidence: 94%
See 2 more Smart Citations
“…6c) colocalize with GnRHRs in the limited area of the plasma membrane in bovine gonadotrophs. The positive overlap coefficient calculated by confocal data analysis software was very strong (more than 0.70) between GnRHR and GPR61, between GnRHR and GPR153, and between GnRHR and AMHR2 on the cell-surface of gonadotrophs [33][34][35].…”
Section: Colocalization Of Gpr61 Gpr153 and Amhr2 With Gnrhr In Thementioning
confidence: 94%
“…Real-time PCR and western blot analyses found that GPR153 expression was significantly lower in AP tissues during the early luteal phase as compared to pre-ovulation or the late luteal phases [34]. The 5ꞌ-flanking region of the GPR153 gene contained a consensus response element sequence for estrogen, but not for progesterone [34]. None of the few reports published describe the function of GPR153 or identify its ligand(s).…”
Section: Bovine Gonadotrophs Express Gpr153mentioning
confidence: 99%
See 1 more Smart Citation
“…The lipid rafts are distinct, relatively insoluble regions that have lower density and are less fluid than surrounding membrane (Simons et al 2000;Head et al 2014), and they facilitate signaling by allowing colocalization of membrane receptors and their downstream signaling components (Simons et al 2000;Head et al 2014). We recently discovered that two orphan receptors, GPR61 and GPR153, are colocalized with GnRHR in gonadotroph plasma membrane lipid rafts (Pandey et al 2017a(Pandey et al , 2017b. Therefore, gonadotroph lipid rafts containing GnRHR may contain AMHR2.…”
Section: Introductionmentioning
confidence: 99%
“…We used also a specific guinea pig polyclonal anti-bovine GnRHR (Kadokawa et al 2014), a specific mouse monoclonal anti-LH β (LHβ) subunit antibody (clone 518-B7; Matteri et al 1987;Iqbal et al 2009), and a specific mouse monoclonal anti-FSH β (FSHβ) subunit antibody (clone A3C12; Borromeo et al 2004) for immunohistochemical analysis of AP tissue. These antibodies are utilized for immunohistochemical analysis of AP tissue in our previous papers (Kadokawa et al 2014;Pandey et al 2017aPandey et al , 2017bKereilwe et al 2018) Western Blotting for AMH detection Proteins were extracted from the AP (n = 4) or ovary samples (n = 4, used as positive controls) and western blotting was performed as previously described (Kereilwe et al 2018). The extracted protein sample (33.4µg of total protein in 37.5µl) was mixed in…”
Section: Antibodies Used In This Studymentioning
confidence: 99%